2007
DOI: 10.1111/j.1600-0463.2007.apm_601.x
|View full text |Cite
|
Sign up to set email alerts
|

Low frequency of BK virus in prostatic adenocarcinomas

Abstract: BK virus (BKV) exhibits many oncogenic properties and has been associated with a variety of tumors in humans. BKV has not been well studied in the context of prostate neoplasia; however, an association of BKV with prostatic adenocarcinoma has been suggested based on the detection of viral DNA sequences and expression of viral proteins in clinical samples. To further investigate the reported association of BKV with prostatic adenocarcinoma and the potential role of the virus in prostate tumorigenesis, 30 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 26 publications
(47 reference statements)
1
19
0
Order By: Relevance
“…Zambrano et al demonstrated the presence of BKV DNA in 3/12 prostate specimens by utilizing PCR (94), and Lau et al detected BKV DNA in tumor cells in 2/30 prostate specimens using ISH (43). Our previous study, however, was the first to demonstrate the presence of both viral DNA and oncoprotein expression in PIA lesions of neoplastic prostates (17).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Zambrano et al demonstrated the presence of BKV DNA in 3/12 prostate specimens by utilizing PCR (94), and Lau et al detected BKV DNA in tumor cells in 2/30 prostate specimens using ISH (43). Our previous study, however, was the first to demonstrate the presence of both viral DNA and oncoprotein expression in PIA lesions of neoplastic prostates (17).…”
Section: Discussionmentioning
confidence: 71%
“…There are two additional reports on the presence of BKV DNA in prostate carcinomas (43,94). Zambrano et al demonstrated the presence of BKV DNA in 3/12 prostate specimens by utilizing PCR (94), and Lau et al detected BKV DNA in tumor cells in 2/30 prostate specimens using ISH (43).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of these findings, it has been proposed that BKV may be involved in the development of various cancers in humans [75][76][77] and recently Das et al hypothesized that BKV acts as a cofactor in the development of prostate cancer [78,79]. However, the two reports that attempted to confirm these findings based on histochemistry and in situ hybridisation are contradictory [80,81].…”
Section: Japanese Ancestors (The Yayoi Immigrants) Came Through the Kmentioning
confidence: 90%
“…While they did not observe T Ag expression by IHC in any of their samples, ISH revealed the presence of BKV DNA in four non-neoplastic, two neoplastic and one PIN tissues. 92 There are also negative reports regarding the potential association between BKV and prostate cancer in the literature. Using nested PCR, Sfanos et al analyzed a total of 338 samples from 200 patients and found only one sample positive for BKV; 93 Akgul and colleagues detected the BKV genome in one out of 85 PCA analyzed tissue samples; 94 Bergh and colleagues did not amplify the BKV genome in either 171 prostate cancer tissues nor in 181 control tissues.…”
Section: Discussionmentioning
confidence: 99%